DEFINITION AND ESSENCE ANALYSIS OF PUBLIC-PRIVATE PARTNERSHIP (PPP) MODEL - Bo Liu, Xuehan Ma, Yun Li & Liang Tang (International Journal of Research Science and Management, 2020)
PPP model has become an important means to reduce the financial burden in the new normal, and PPP model in China has a certain difference with the PPP model overseas. Based on the analysis of the characteristics of PPP model, the definition of PPP model according with realistic of China is proposed; the advantages of PPP model are analyzed from helping the transformation of government functions, promoting investment diversification, and reasonable risk allocation etc.; through analysis of partnership concept, the essence of PPP model is put forward, which is the complementary advantages of the government and social capital.